PERANAN PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PEMBAYARAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) ATAS TRANSAKSI JUAL BELI TANAH DAN/ATAU BANGUNAN DI KABUPATEN SAMOSIR - ADA TUA SIMBOLON (PREMISE LAW JURNAL, 2016)
Legal act on land and building rights acquisition must have AJB made by and before PPAT who has the authority to organize land and building transact. Based on Article 91, paragraphs 1 and 3 of Law on PDRD, a PPAT can only sign Transact Certificate after a taxpayer submits the evidence of tax payment. Otherwise, a sanction will be imposed upon him, based on Article 93, paragraphs 1 and 3 juncto Article 11, paragraphs 1 and 3 of Perda  of Samosir Regency Number. 9/2011 on BPHTB. PPAT has to be liable for supervising BPHTB tax payment. the sanction when he fails to do his job in supervising of BPHTB tax payment in Samosir Regency varies. However, in Law Number. 28/2009 on PDRD juncto Perda of Samosir Regency Number. 9/2011 on BPHTB does not strictly regulate legal procedure on the sanction Keywords: Role of PPAT, BPHTB Tax, Land Transaction